SOTERIOLOGI: SEBUAH KAJIAN TEOLOGI REFORMED - Gulo, Manase (Manna Rafflesia, 2015)
Understanding salvation is an urgent finality for human life. Because by understanding clearly human safety is not trapped into the practice of life which imposes itself. Therefore the presentation of the doctrine of Salvation from the perspective of Reform Theology is expected to help believers be able to interpret the salvation received from Jesus Christ. The doctrine of salvation is an important part of thinking about the Christian faith. Because the doctrine provides direction and certainty how human life is saved. At present there is a great deal of understanding being raised regarding the doctrine of salvation. Therefore, through this paper, we explain the doctrine of salvation from the perspective of Reformed Theology. Why? Because this theology has been proven time-tested and persists in strong soteriological teachings. May through this writing the insight of believers soteriology can be deeper.